Kinetics of the incorporation of the main phenolic compounds into the lignan macromolecule during flaxseed development. (15th February 2017) - Ramsay, Aina; Fliniaux, Ophélie; Quéro, Anthony; Molinié, Roland; Demailly, Hervé; Hano, Christophe; Paetz, Christian; Roscher, Albrecht; Grand, Eric; Kovensky, José; Schneider, Bernd; Mesnard, François
Highlights: Temporal quantification of the main phenolics in developing flaxseed. Determination of free or bound phenolics in flax lignan macromolecule. Monolignols are not ester linked to the lignan macromolecule. Secoisolariciresinol diglucoside is mainly bound to the macromolecule but also free. Identification of ( z )-ferulic acid in flaxseed macromolecule lignan. Abstract: The main flax lignan, secoisolariciresinol diglucoside, is stored in a macromolecule containing other ester-bound phenolic compounds. In this study, NMR and HPLC-UV analyses were performed on flaxseeds harvested at different developmental stages to identify and quantify the main phenolic compounds produced during seed development. Extraction was carried out with or without alkaline hydrolysis to determine if these molecules accumulate in the lignan macromolecule and/or in a free form. Monolignol glucosides accumulate in a free form up to 9.85 mg/g dry matter at the early developmental stages. Hydroxycinnamic acid glucosides and flavonoid accumulate (up to 3.18 and 4.07 mg/g dry matter, respectively) in the later developmental stages and are ester-bound in the lignan macromolecule. Secosiolariciresinol diglucoside accumulates (up to 28.65 mg/g dry matter) in the later developmental stages in both forms, mainly ester-bound in the lignan macromolecule and slightly in a free form.